2019
DOI: 10.1016/j.isci.2019.07.002
|View full text |Cite
|
Sign up to set email alerts
|

von Hippel-Lindau Protein Maintains Metabolic Balance to Regulate the Survival of Naive B Lymphocytes

Abstract: Summary B lymphocytes undergo metabolic reprogramming upon activation to meet the bioenergetic demands for proliferation and differentiation. Yet, little is known if and how the fate of naive B cells is metabolically regulated. Here, we specifically delete von Hippel-Lindau protein (VHL) in B cells using CD19-Cre and demonstrate that metabolic balance is essential for naive B cell survival. Loss of VHL disturbs glycolytic and oxidative metabolic balance and causes severe reduction in mature B cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 46 publications
(56 reference statements)
2
22
1
Order By: Relevance
“…NK cells were treated with IL-10 in the presence or absence of rapamycin for 16 h as indicated. Real-time analyses of ECAR and OCR of treated and non-treated NK cells were performed using XF-24 Extracellular Flux Analyzer (Seahorse Bioscience) as described previously ( 31 ). Briefly, NK cells were resuspended in XF base and assay medium (Agilent Technologies) for ECAR and OCR analysis, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…NK cells were treated with IL-10 in the presence or absence of rapamycin for 16 h as indicated. Real-time analyses of ECAR and OCR of treated and non-treated NK cells were performed using XF-24 Extracellular Flux Analyzer (Seahorse Bioscience) as described previously ( 31 ). Briefly, NK cells were resuspended in XF base and assay medium (Agilent Technologies) for ECAR and OCR analysis, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In accordance, we observed a stabilization of HIF1in DNT B cells at d3 of LPS stimulation under normoxic conditions (Figure 9a, b). The increased HIF1 protein abundance suggested increased reductive decarboxylation of -ketoglutarate to citrate and the generation of long chain acylcarnitines (Xu et al, 2019), but our measurements indicated that citrate was not increased (Figure 8 f, g). Therefore, we reasoned that the driving force of the intact SDH complex II shifts the equilibrium of the TCA cycle away from citrate generated through reductive carboxylation of -ketoglutarate towards the conversion of -ketoglutarate to succinate (see Figure S5 for illustration).…”
Section: The Mitochondrial Respiratory Chain In Plasmablasts Coordinamentioning
confidence: 67%
“…This would increase HIF1 abundance without concomitantly increasing citrate. Since HIF1 normally increases lipid synthesis in B cells via citrate (Xu et al, 2019), de novo lipid biosynthesis should be altered in DNT-expressing B cells.…”
Section: The Mitochondrial Respiratory Chain In Plasmablasts Coordinamentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike glomerulonephritis, erythropoietin production may be elevated in RCC [ 94 ] and B cells are not commonly detected in RCC [ 95 ]. These latter inverse manifestations between the diseases may be associated with the differential expression of hypoxic cell signals that induce the production of erythropoietin [ 94 ] and promote B cell apoptosis [ 96 ].…”
Section: Introductionmentioning
confidence: 99%